2010
DOI: 10.1074/jbc.m109.043117
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase-activating Polypeptide (PACAP)/PAC1HOP1 Receptor Activation Coordinates Multiple Neurotrophic Signaling Pathways

Abstract: MAPK and Akt pathways are predominant mediators of trophic signaling for many neuronal systems. Among the vasoactive intestinal peptide/secretin/glucagon family of related peptides, pituitary adenylate cyclase-activating polypeptide (PACAP) binding to specific PAC1 receptor isoforms can engage multiple signaling pathways and promote neuroprotection through mechanisms that are not well understood. Using a primary sympathetic neuronal system, the current studies demonstrate that PACAP activation of PAC1HOP1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 89 publications
11
80
0
Order By: Relevance
“…The broad spectrum PKC inhibitor Ro 318220 inhibited PACAP-27-induced TG2 activity, indicating that Gq-protein coupling is involved in PAC1 receptor-mediated TG2 activation. The PAC1 receptor also activates ERK1/2, JNK1/2, p38 MAPK and PKB (Monaghan et al, 2008;May et al, 2010, Castorina et al, 2014. In this study we observed PACAP-27-induced activation of ERK1/2, JNK1/2, and PKB but not p38 MAPK.…”
Section: Role Of Protein Kinases In Pac1 Receptor-mediated Tg2 Activasupporting
confidence: 53%
See 2 more Smart Citations
“…The broad spectrum PKC inhibitor Ro 318220 inhibited PACAP-27-induced TG2 activity, indicating that Gq-protein coupling is involved in PAC1 receptor-mediated TG2 activation. The PAC1 receptor also activates ERK1/2, JNK1/2, p38 MAPK and PKB (Monaghan et al, 2008;May et al, 2010, Castorina et al, 2014. In this study we observed PACAP-27-induced activation of ERK1/2, JNK1/2, and PKB but not p38 MAPK.…”
Section: Role Of Protein Kinases In Pac1 Receptor-mediated Tg2 Activasupporting
confidence: 53%
“…Likewise, PACAP is widely recognized as a neuroprotective peptide and potential therapeutic agent for the treatment of cerebral ischaemia and various neurodegenerative disorders (Reglodi et al, 2011;Lee and Seo, 2014). The mechanisms of PACAP/PAC1 receptorinduced neuroprotection are complex and involve multiple signalling pathways that include PKA, PKB, ERK1/2, NF-кB and Ca 2+ mobilization (May et al, 2010;Baxter et al, 2011;Manecka et al, 2013). In this study we have shown for the first time a role for TG2 in PAC1 receptor-induced cytoprotection in differentiating mouse N2a and human SH-SY5Y neuroblastoma cells.…”
Section: Role Of Tg2 In Pac1 Receptor-induced Cytoprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…PACAP activation of PAC1 HOP1 caused ERK1/2 and ERK5 activation, but abrogated stress-activated protein/c-Jun NH 2 -terminal kinase and p38 mitogen-activated protein kinase signaling (May et al, 2010). PACAP caused ERK1/2 and ERK5 phosphorylation of primary sympathetic neurons within minutes and phosphorylation of AKT within hours (May et al, 2010).…”
Section: Addition Colony Numbermentioning
confidence: 99%
“…PACAP activation of PAC1 HOP1 caused ERK1/2 and ERK5 activation, but abrogated stress-activated protein/c-Jun NH 2 -terminal kinase and p38 mitogen-activated protein kinase signaling (May et al, 2010). PACAP caused ERK1/2 and ERK5 phosphorylation of primary sympathetic neurons within minutes and phosphorylation of AKT within hours (May et al, 2010). We are investigating whether PACAP causes AKT phosphorylation in NSCLC cells, but we recently found that PACAP causes focal adhesion kinase and paxillin tyrosine phosphorylation within minutes after the addition to NCI-H838 cells (Moody et al, 2012).…”
Section: Addition Colony Numbermentioning
confidence: 99%